The canonical Notch pathway effector RBP‐J regulates neuronal plasticity and expression of GABA transporters in hippocampal networks. Issue 5 (27th March 2015) - Liu, Shuxi; Wang, Yue; Worley, Paul F.; Mattson, Mark P.; Gaiano, Nicholas
ABSTRACT Activation of the Notch pathway in neurons is essential for learning and memory in various species from invertebrates to mammals. However, it remains unclear how Notch signaling regulates neuronal plasticity, and whether the transcriptional regulator and canonical pathway effector RBP‐J plays a role. Here, we report that conditional disruption of RBP‐J in the postnatal hippocampus leads to defects in long‐term potentiation, long‐term depression, and in learning and memory. Using gene expression profiling and chromatin immunoprecipitation, we identified two GABA transporters, GAT2 and BGT1, as putative Notch/RBP‐J pathway targets, which may function downstream of RBP‐J to limit the accumulation of GABA in the Schaffer collateral pathway. Our results reveal an essential role for canonical Notch/RBP‐J signaling in hippocampal synaptic plasticity and suggest that role, at least in part, is mediated by the regulation of GABAergic signaling. © 2014 Wiley Periodicals, Inc.